Genetic and environmental dispersion parameter estimation by test interval method in dairy sheep - Komprej, Andreja (Acta agriculturae Slovenica, 2011)
Genetic and environmental parameters for 38 983 test-day records of daily milk yield (DMY), fat (FC) and protein (PC) content, collected between 1994 and 2002, were estimated on 3,068 dairy ewes of the three Slovenian breeds. A multivariate restricted maximum likelihood method was used for estimation, where every test-day record was treated as a different trait. Fixed part of the multitrait animal model for DMY, FC, and PC included breed and lambing season as classes, while stage of lactation, parity, and litter size were covariates. Random part of the model contained additive genetic effect and the effects of flock test month and permanent environment over lactations. Heritability estimates for individual test-days were between 0.10 and 0.23 for DMY, 0.09 and 0.18 for FC, and 0.19 and 0.28 for PC. The flock test month effect explained most of the phenotypic variance: 0.18 to 0.41 for DMY, 0.26 to 0.45 for FC, and 0.24 to 0.44 for PC. A lower variance ratio was explained by the permanent environment effect over lactations: 0.09 to 0.15 for DMY, 0.02 to 0.11 for FC, and 0.02 to 0.09 for PC. Additive genetic correlations between individual test-days were high in all three milk traits for adjacent months of lactation. They decreased when the interval between months of lactation increased. The structure of additive genetic correlations showed that the observed milk traits in the different stages of lactation were genetically not the same trait, since the correlations between distant months of lactation were lower than one.
Keywords: ovce; mlečnost; mleko; sestava; genetski parametri; okoljski parametri; metoda z intervali